The Effect of Physical Exercise Psychology on Behaviour Control of College Students - Huafeng Zhou; Xingquan Chen, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
Within the demographic of college students, characterized by elevated educational attainment and self-regard, there typically exists a propensity towards heightened ambitions compared to their non-academic peers. However, this cohort also contends with escalated psychological strain due to intensified competition within their academic spheres. This study sought to elucidate the impact of physical exercise psychology on the behavioural regulation of college students amidst these demanding circumstances. A sample comprising 170 college students enrolled in a conventional university was selected via random sampling methodology. A total of 170 questionnaires were distributed, achieving a complete recovery rate of 100%. Notably, no instances of invalid questionnaires, characterized by incorrect or incomplete responses, were encountered, resulting in a 100% questionnaire effectiveness rate. Subsequently, participants completed the administered questionnaires and engaged in experimental protocols designed to assess levels of exercise intention, executive function, and other pertinent variables. The outcomes of a multiple regression analysis revealed that exercise attitude, subjective norms, and behavioural control collectively elucidated 70% of the variance in exercise intention. Furthermore, exercise intention and the perception of behavioural control explicated 37% of the behavioural variance. For instance, college students, in contrast to their counterparts, exhibit pronounced autonomy and possess a heightened comprehension of the advantages of exercise, coupled with proficient mastery of exercise techniques. Consequently, within the context of college students, the theory of planned behaviour assumes a prominent role in forecasting both intention and subsequent behaviour. The psychological well-being of college students not only impacts their academic performance and campus life but also exerts a direct influence on their long-term personal development. To foster the mental health advancement of college students, it is imperative for society, educational institutions, and families to allocate considerable attention and resources. This study further enriches the existing body of literature by providing comprehensive insights that may serve as a valuable resource for researchers seeking to delve into novel avenues of inquiry within the realm of physical exercise psychology and its implications for behavioural regulation among students.